Rahiki [Ö.953/1546] ve şiirleri - (:unkn) unknown (My University, 2009)
Bu makalede, on altıncı asır şairlerinden Rahîkî’nin hayatı ve edebî kişiliği hakkında bilgi verilmiş, mecmualardan derlenen şiirlerinin tenkitli metni sunulmuştur. Ayrıca metinde geçen bazı noktalar açıklanmaya çalışılmıştır.

In this article has been given informations about Rahîkî who was one of the poets of sixteenth century and his literary personality. Also it has been prepared critical editions of the Rahîkî’s poems which has been collected from mecmuas. Beside, some points in text has been explained.
Rahiki and his poems
Keywords: Edebiyat